A experiência estética no Cerrado para a formação de valores estéticos e éticos na educação ambiental - Iared, Valéria Ghisloti (2015)
Our world views are based on principles, feelings, emotions that go through a dimension of human life which involve ethical and aesthetic values. However, the formation of values is a less explicit dimension of environmental education compared to the appropriation of knowledge. Some studies confirm the relative silence of aesthetic considerations in the literature and curriculum, so this topic has the potential to be further explored in research and in environmental education practice. Based on an interpretative perspective, we assume as aesthetic experience the possibility of our bodies engaged in the world to realize and create meanings of all forms of existence. From this, this study aims to understand the nature of aesthetic experience in the Cerrado, due to its history of occupation and degradation. In this research, we transition between the modern and post-modern paradigm in order to deeply understand the meaning of aesthetic experience. This transition is the result of our study pathway which was willing to seek for approaches and methods to answer the research question. Therefore, our data collection was carried out using two techniques: 17 semistructured interviews (understood in a modern paradigm, but interpreted together with the research participants) and a walking ethnography in the Cerrado (located as a post- modern methodology), which 08 participants who had already been interviewed were present, and 04 out of 08 were part of the data collection The participants were invited following the criteria of a life story related to the Cerrado, reflecting on a love involvement regarding this environment.The results indicated that the informal and spontaneous experiences in nature, moments of conflict and dialogue were significant for the development of an affective bond and an ethical stance towards the Cerrado. The walking ethnography put the prospect of analyzing the aesthetic experience of the participants moving in the Cerrado and the researcher was also engaged in the aesthetic experience of the Cerrado along with the participants. Instead of being a dialogical and verbal action, this activity is embodied and the focus is the multisensorial experience which involves multi-dimensions of corporality and connections with the materialities of the more than human world. The data that emerged during the walk in the Cerrado supplemented the interviews. In addition, we identified that the participants of this study had an ethical position in relation to the Cerrado, which we attributed to be from the dialogue among participants and family, friends, coworkers and text readings. However, this relationship can not be considered the same in other groups of people, situations and contexts. Therefore, new research questions that continue investigating the relations between aesthetic experience and ethics are necessary.